PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP LUAS PENGUNGKAPAN KOMPENSASI MANAJEMEN KUNCI DI LAPORAN KEUANGAN - Akmyga, Stalsa Frani; Mita, Aria Farah (UI Scholars Hub, 2015)
Corporate governance has impacts on the disclosure of key management compensation in the financial statements through the application of the principle of transparancy. This research aims to analyze the impact of corporate governance structure, such as family ownership, managerial ownership and the effectiveness of the audit committee, as well as audit quality of key management compensation disclosures in the financial statements according to PSAK No. 7 (Revised 2010). The research using multiple regressions examined non-financial companies listed on the Indonesia Stock Exchange in 2011. The research found that companies that are controlled by family and not part of a business group significantly affect management to comply with the mandatory disclosure related to key management compensation information in the financial statements. The research also found that the effectiveness of the audit committee significantly affects management to provide better information related to financial disclosures. Furthermore, the audit quality significantly increases the transparency of the compensation of key management related to PSAK No. 7 (Revised 2010).